(212)Pb-Labeled Antibody 225.28 Targeted to Chondroitin Sulfate Proteoglycan 4 for Triple-Negative Breast Cancer Therapy in Mouse Models - Kasten, Benjamin B. (Int J Mol Sci, 2018)
Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with a poor prognosis. There is a clinical need for effective, targeted therapy strategies that destroy both differentiated TNBC cells and TNBC cancer initiating cells (CICs), as the latter are implicated in the metastasis and recurrence of TNBC. Chondroitin sulfate proteoglycan 4 (CSPG4) is overexpressed on differentiated tumor cells and CICs obtained from TNBC patient specimens, suggesting that CSPG4 may be a clinically relevant target for the imaging and therapy of TNBC. The purpose of this study was to determine whether α-particle radioimmunotherapy (RIT) targeting TNBC cells using the CSPG4-specific monoclonal antibody (mAb) 225.28 as a carrier was effective at eliminating TNBC tumors in preclinical models. To this end, mAb 225.28 labeled with (212)Pb ((212)Pb-225.28) as a source of α-particles for RIT was used for in vitro Scatchard assays and clonogenic survival assays with human TNBC cells (SUM159 and 2LMP) grown as adherent cells or non-adherent CIC-enriched mammospheres. Immune-deficient mice bearing orthotopic SUM159 or 2LMP xenografts were injected i.v. with the targeted (225.28) or irrelevant isotype-matched control (F3-C25) mAbs, labeled with (99m)Tc, (125)I, or (212)Pb for in vivo imaging, biodistribution, or tumor growth inhibition studies. (212)Pb-225.28 bound to adherent SUM159 and 2LMP cells and to CICs from SUM159 and 2LMP mammospheres with a mean affinity of 0.5 nM. Nearly ten times more binding sites per cell were present on SUM159 cells and CICs compared with 2LMP cells. (212)Pb-225.28 was six to seven times more effective than (212)Pb-F3-C25 at inhibiting SUM159 cell and CIC clonogenic survival (p < 0.05). Radiolabeled mAb 225.28 showed significantly higher uptake than radiolabeled mAb F3-C25 in SUM159 and 2LMP xenografts (p < 0.05), and the uptake of (212)Pb-225.28 in TNBC xenografts was correlated with target epitope expression. (212)Pb-225.28 caused dose-dependent growth inhibition of SUM159 xenografts; 0.30 MBq (212)Pb-225.28 was significantly more effective than 0.33 MBq (212)Pb-F3-C25 at inhibiting tumor growth (p < 0.01). These results suggest that CSPG4-specific (212)Pb-225.28 is a useful reagent for RIT of CSPG4-expressing tumors, including metastatic TNBC.